Kenya’s Political Regime in Need of a Humanizing Pedagogy: what to Learn from Paulo Freire’s Pedagogy of the Oppressed - Amukowa, Wycliffe; Atancha, Jeremiah (American International Journal of Contemporary Research, 2013)
Fatalism in the guise of docility is the fruit of an historical and sociological situation, not an essential characteristic of a people's behavior. It almost always is related to the power of destiny or fate or fortune— inevitable forces—or to a distorted view of God. The oppressed see their suffering, the fruit of exploitation, as the will of God. Submerged in reality, the oppressed cannot perceive clearly the "order" which serves the interests of the oppressors whose image they have internalized. Chafing under the restrictions of this order, they often manifest a type of horizontal violence, striking out at their own comrades for the pettiest reasons (Freire, 2005). Build on this thought, this paper endeavors a theorization into the Kenya’s desire for a liberating political regime. The paper founds itself on Paulo Freire’s Pedagogy of the Oppressed.
Keywords: Election; Liberation; Oppression; Pedagogy; Political; Violence